Implementasi Metode Bermain Sebagai Strategi Peningkatan Keaktifan Gerak dalam Pembelajaran PJOK di SD S Pelangi - Suyono Suyono; Jihan Na’imah Ritonga; Raudhatul Jannah; Miranda Tambunan; Ratmini Pasaribu (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2026)
This study aims to analyze the effectiveness of play-based methods in Physical Education, Sports, and Health (PJOK) learning for sixth-grade students at Pelangi Elementary School. The background of this study is the decline in movement motivation in upper-grade students due to excessive focus on academic workload. The research method used is descriptive qualitative with data collection techniques in the form of participatory observation and in-depth interviews with key informants. The results of the study indicate that the integration of structured games in the Lesson Implementation Plan (RPP) can improve motor coordination and students' social values. In addition, modifications to game tools and rules provide creative solutions to overcome the limitations of existing facilities. The conclusion of the study confirms that the play-based approach functions not only as a recreational activity but also as an effective formal instructional method to achieve curriculum targets holistically, supporting students' physical and social development simultaneously. This approach is expected to be implemented more widely in schools to improve the quality of PJOK learning.